“Yeah, absolutely and totally”: boosters and gender differences in student-supervisor consultations - Ahmed, Wasan Khalid; Kesumawati A.Bakar,; Alkhawaja, Hussein W. H. (Penerbit Universiti Kebangsaan Malaysia, 2023)
Student-supervisor consultation is an essential academic requirement for Arab EFL male and female students to pass their postgraduate degree in Malaysian universities. During these consultations, students negotiate with their supervisors about their theses or final projects. However, these consultations form a challenge to these students as they need to demonstrate appropriate linguistic knowledge while corresponding to their supervisors’ comments and corrections. One aspect of the linguistic challenge is the use of boosters as any over or misuse of these devices can be interpreted as inappropriate behavior, thus might affect the student-supervisor relationships and cause communication breakdown. The purpose of this study was to determine the types, frequencies, and functions of boosters in relation to gender as used by these students during the academic consultations. The data were collected by means of eight naturally occurring consultations and a pragmatic knowledge questionnaire and then analyzed quantitatively and qualitatively. The findings showed that the students used a variety of boosting devices with the intensifying adverbs, style adjuncts, and factive verbs being the most frequent. The gender analysis revealed differences in the types and counts of boosters with the male students generally using significantly higher frequencies of boosters than the female students. The pragmatic analysis showed that the Arab students used boosters strategically to reinforce their speech, so that they show their knowledge and appear more convincing. Further, the use of the boosters was not meant by the students to express polite or impolite behaviors, but it was mainly an appropriate politic behavior.